2019
DOI: 10.1186/s12864-019-5461-3
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of the longan transcriptome reveals distinct regulatory programs during the floral transition

Abstract: BackgroundLongan (Dimocarpus longan Lour.) is an important fruit tree in the subtropical regions of Southeast Asia and Australia. Among the factors affecting D. longan fruit yield, the difficulty and instability of blossoming is one of the most challenging issues. Perpetual flowering (PF) is a crucial trait for fruit trees and is directly linked to production potential. Therefore, studying the molecular regulatory mechanism of longan PF traits is crucial for understanding and solving problems related to flower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 104 publications
0
40
0
Order By: Relevance
“…'Shixia' and 'Lidongben' are common longan varieties exhibiting seasonal flowering traits, while 'Sijimi' is a specific variety with continuous flowering trait. Firstly, the expression patterns of 17 DlARF genes were analyzed using RNA-seq databases of apical buds during floral bud development in 'Shixia' [33]. In Guangdong Province of China, apical buds in November are at the stage of before the emergence of floral primordia, apical buds in December are at the stage of floral organ differentiation which is characterized by the appearance of red dot, and apical buds in January is characterized by the appearance of the first inflorescence [33].…”
Section: Expression Profiles Of Dlarf Genes In Different Longan Variementioning
confidence: 99%
See 2 more Smart Citations
“…'Shixia' and 'Lidongben' are common longan varieties exhibiting seasonal flowering traits, while 'Sijimi' is a specific variety with continuous flowering trait. Firstly, the expression patterns of 17 DlARF genes were analyzed using RNA-seq databases of apical buds during floral bud development in 'Shixia' [33]. In Guangdong Province of China, apical buds in November are at the stage of before the emergence of floral primordia, apical buds in December are at the stage of floral organ differentiation which is characterized by the appearance of red dot, and apical buds in January is characterized by the appearance of the first inflorescence [33].…”
Section: Expression Profiles Of Dlarf Genes In Different Longan Variementioning
confidence: 99%
“…Firstly, the expression patterns of 17 DlARF genes were analyzed using RNA-seq databases of apical buds during floral bud development in 'Shixia' [33]. In Guangdong Province of China, apical buds in November are at the stage of before the emergence of floral primordia, apical buds in December are at the stage of floral organ differentiation which is characterized by the appearance of red dot, and apical buds in January is characterized by the appearance of the first inflorescence [33]. The results showed that there were nine DlARFs (DlARF-1,-2,-4,-6,-8,-9,-10,-11,-16) that showed higher transcript levels in November and December in 'Shixia' (Figure 6a).…”
Section: Expression Profiles Of Dlarf Genes In Different Longan Variementioning
confidence: 99%
See 1 more Smart Citation
“…The discovery the AS events of DlSTs, we use three transcriptome databases, including one for different longan varieties ('Sijimi' and 'Lidongben') [64], one for different floral bud development stages in 'Shixia' cultivar [65], and one 'Sijimi' transcriptome database containing nine longan tissues [59]. The quality of RNA-seq data are listed in Table S4.…”
Section: Identification Of Alternative Splicing (As) Eventsmentioning
confidence: 99%
“…Variety breeding has always been important for improving longan production, typically targeting two main traits, size and sweetness of the fruit 18, 19 . The breeding and extension of excellent varieties can enhance the stress resistance of fruit trees, improve the fruit quality and expand the planting area.…”
Section: Introductionmentioning
confidence: 99%